Dynamics and Stagnation in the Malthusian Epoch - Ashraf, Quamrul; Galor, Oded (American Economic Review, 2011)
This paper examines the central hypothesis of the influential Malthusian theory, according to which improvements in the technological environment during the pre-industrial era had generated only temporary gains in income per capita, eventually leading to a larger, but not significantly richer, population. Exploiting exogenous sources of cross-country variations in land productivity and the level of technological advancement the analysis demonstrates that, in accordance with the theory, technological superiority and higher land productivity had significant positive effects on population density but insignificant effects on the standard of living, during the time period 1-1500 CE.